Malay and Islamic traditions elements through the paintings of Mastura Abdul Rahman, Ruzaika Omar Basareee and Haron Mokhtar - Ahmad Hakim Abdullah; Yuhanis Ibrahim; Mohammed Iqbal Badaruddin (Ikatan Ahli Arkeologi Malaysia, Universiti Kebangsaan Malaysia, 2021)
This study will highlight the elements of Islamic values and Malay traditions in the artworks of 20th and 21st-century Malaysian artists, namely Mastura Abdul Rahman, Haron Mokhtar, and Ruzaika Omar Basaree by discussing the elements of Malay values and Islamic traditions in respect of their artworks. The analyses focused on the artworks from 1980 to 2014, specifically Haron Mokhtar’s “Zahir Mosque”, Ruzaika Omar Basaree’s “Siri Dungun” and Mastura Abdul Rahman’s “House of Harmony” and “Interior No. 29”. These artists’ works were delivered according to the manifestation of the National Cultural Policy 1971, which highlighted the Islamic and local identity as the main idea and theme of the artworks of local artists. This study has used qualitative methods, which are interviews and observations of each work in the artists’ catalogue as a process of collecting primary data. Meanwhile, secondary data were gathered through referencing academic works like books, journals, and magazines on Islamic values and Malay traditions in visual arts paintings. The analyses found that these works used Islamic art elements, like the “Thuluth” khat in “Zahir Mosque”, as well as the combination of colour and flora motifs on “Siri Dungun”. At the same time, they feature cultural elements, such as “congkak” and “Labu sayong” and traditional Malay ornamental design, which represent the Malay culture and philosophies.